Graphene-based hydrogen sulfide gas sensor and preparation method thereof

By using a laser beam to irradiate a wooden substrate at room temperature to form graphene and disperse bimetallic oxide nanoparticles, a simple and environmentally friendly graphene-based hydrogen sulfide gas sensor was prepared, which solved the problems of complex preparation and poor selectivity in the existing technology and achieved high-sensitivity and high-selectivity hydrogen sulfide gas detection.

CN120721807AActive Publication Date: 2025-09-30TIANJIN UNIV

Patent Information

Application Number
CN202511234798.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-09-30
Estimated Expiration
2045-09-01

AI Technical Summary

Technical Problem

The existing graphene-based hydrogen sulfide gas sensor has a complex preparation process, slow response speed and poor selectivity, is inconvenient to operate under high temperature and high pressure conditions, and is expensive, which limits its application in hydrogen sulfide gas detection.

Method used

A laser beam is used to irradiate a wooden substrate at room temperature to crack lignin and cellulose to form graphene, and bimetallic oxide nanoparticles are dispersed on its surface. This layer is combined with a conductive material to form a sensitive layer to prepare a graphene-based hydrogen sulfide gas sensor.

Benefits of technology

A simple and environmentally friendly preparation process has been achieved, which can detect hydrogen sulfide gas with high sensitivity and selectivity at room temperature and is suitable for ppb-level hydrogen sulfide gas detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120721807A_ABST
    Figure CN120721807A_ABST
Patent Text Reader

Abstract

The invention provides a graphene-based hydrogen sulfide gas sensor and a preparation method thereof, and relates to the technical field of gas sensors. The preparation method of the graphene-based hydrogen sulfide gas sensor comprises the following steps: soaking the wood substrate in a mixed metal salt solution containing a water-soluble silver salt and a water-soluble transition metal salt; irradiating the soaked wood substrate by using a laser beam at room temperature under the condition of no shielding gas, so that lignin and cellulose in the wood substrate are cracked and reconstructed to form graphene; meanwhile, the mixed metal salt immersed in the wood substrate is decomposed to form bimetallic oxide nanoparticles including silver oxide nanoparticles and transition metal oxide nanoparticles, and the bimetallic oxide nanoparticles are dispersed on the surface of each layer of graphene to obtain a sensitive layer; and coating conductive materials on the wooden substrate and on the two sides of the sensitive layer to form a connecting electrode in contact with the sensitive layer, thereby obtaining the graphene-based hydrogen sulfide gas sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas sensors, and more particularly, to a graphene-based hydrogen sulfide gas sensor and a preparation method thereof. Background Art

[0002] Hydrogen sulfide (H2S), a colorless, highly toxic gas with a rotten egg smell, is widely found in crude oil exploration wells, oil refineries, sewer systems, biogas pools, and landfills. It is corrosive to industrial equipment and poses a serious threat to human health. The national standard stipulates that the maximum allowable concentration of hydrogen sulfide in the air is 10 mg / m 3 (7 ppm). Therefore, developing an efficient, sensitive, and economical hydrogen sulfide gas sensor is particularly important. Traditional hydrogen sulfide gas sensors suffer from slow response speeds and poor selectivity. Furthermore, their operating temperatures generally exceed 150°C, posing potential risks when used in hazardous gas environments.

[0003] Graphene has become a highly sought-after material in the field of gas sensing due to its excellent electrical conductivity and its ability to respond to target gases at room temperature. However, graphene itself responds to a variety of gases, but its selectivity is poor, which limits its effectiveness in sensing applications. However, graphene has a large specific surface area, and its selectivity for hydrogen sulfide gas can be improved by modifying its surface with metal oxides or polymer nanoparticles. Some researchers have modified the surface of chemical vapor deposition (CVD) graphene or reduced graphene oxide (RGO) with metal oxide nanoparticles such as copper oxide and tin oxide, as well as polymer nanoparticles such as polyaniline, to improve its response characteristics to hydrogen sulfide gas. However, the preparation process of graphene is relatively complex. CVD graphene needs to be obtained under conditions above 1000°C, and the preparation of the sensor requires complex transfer steps, which is tedious and time-consuming. The preparation process of RGO is also very complex, involving a large amount of hazardous chemicals, which is not conducive to mass production. In addition to the preparation of graphene, the modification process of nanoparticles is also complicated, usually requiring high temperatures above 150°C and hydrothermal conditions of high pressure above 5 bar. It is inconvenient to operate and extremely costly. These factors jointly limit the development of graphene-based hydrogen sulfide gas sensors in practical applications. Summary of the Invention

[0004] To solve at least one of the technical problems in the prior art, an embodiment of the present invention provides a graphene-based hydrogen sulfide gas sensor and a preparation method thereof. The preparation process is simple and environmentally friendly, and the prepared graphene-based hydrogen sulfide gas sensor can detect hydrogen sulfide gas with high sensitivity and high selectivity.

[0005] The present invention provides a method for preparing a graphene-based hydrogen sulfide gas sensor, comprising: immersing a wooden substrate in a mixed metal salt solution containing a water-soluble silver salt and a water-soluble transition metal salt; irradiating the soaked wooden substrate with a laser beam at room temperature without protective gas, so that lignin and cellulose in the wooden substrate are cracked and reconstructed to form graphene, and the mixed metal salt immersed in the wooden substrate is decomposed to form bimetallic oxide nanoparticles, wherein the bimetallic oxide nanoparticles are dispersed on the surface of each graphene layer to obtain a sensitive layer, wherein the bimetallic oxide nanoparticles include silver oxide nanoparticles and transition metal oxide nanoparticles; and coating a conductive material on the wooden substrate and on both sides of the sensitive layer to form connecting electrodes in contact with the sensitive layer to obtain the graphene-based hydrogen sulfide gas sensor.

[0006] Optionally, the wooden substrate is any one of the following: basswood, oak, pine.

[0007] Optionally, the wavelength of the laser beam is 256 nm to 760 nm, and the power of the laser beam is 0.5 W to 10 W.

[0008] Optionally, the water-soluble silver salt includes silver nitrate; the water-soluble transition metal salt includes any one of the following: manganese nitrate, iron nitrate and nickel nitrate.

[0009] Optionally, the concentrations of the water-soluble silver salt and the water-soluble transition metal salt in the mixed metal salt solution are the same, and the concentration of the mixed metal salt solution is 0.1 mol / L to 2 mol / L.

[0010] Optionally, the silver oxide includes silver oxide; and the transition metal oxide includes any one of the following: manganese oxide, iron oxide, and nickel oxide.

[0011] Optionally, the size of the bimetallic oxide nanoparticles is 30 nm to 1000 nm.

[0012] Optionally, the conductive material includes a silver paste material and a metal material.

[0013] According to an embodiment of another aspect of the present invention, a graphene-based hydrogen sulfide gas sensor is also provided, which is prepared by the above-mentioned method for preparing the graphene-based hydrogen sulfide gas sensor. The graphene-based hydrogen sulfide gas sensor includes: a wooden substrate; a sensitive layer formed on the wooden substrate, wherein the sensitive layer is a composite material of graphene and bimetallic oxide nanoparticles; two connecting electrodes are arranged on the wooden substrate, respectively located on both sides of the sensitive layer, and overlapped with the sensitive layer.

[0014] Optionally, the graphene-based hydrogen sulfide gas sensor has a detection range of hydrogen sulfide gas concentration of 25 ppb to 500 ppb.

[0015] According to an embodiment of the present invention, a graphene-based hydrogen sulfide gas sensor and a preparation method thereof are provided. A wooden substrate is immersed in a mixed metal salt solution containing a water-soluble silver salt and a water-soluble transition metal salt. A laser beam is used to irradiate the soaked wooden substrate at room temperature without protective gas. When the laser beam irradiates the surface of the wooden substrate soaked in the mixed metal salt solution, the wooden substrate absorbs the energy of the laser beam. This energy is used to decompose lignin and cellulose in the wooden substrate, and the carbon atoms in the lignin and cellulose are decomposed and reconstructed to form graphene. At the same time, the mixed metal salt immersed in the wooden substrate is decomposed to form bimetallic oxide nanoparticles. The bimetallic oxide nanoparticles are dispersed on the surface of each graphene layer to obtain a sensitive layer with high activity and high selectivity. The bimetallic oxide nanoparticles include silver oxide nanoparticles and transition metal oxide nanoparticles. A conductive material is coated on the wooden substrate and on both sides of the sensitive layer to form connecting electrodes in contact with the sensitive layer to obtain a graphene-based hydrogen sulfide gas sensor. The preparation process is simple and environmentally friendly. The prepared graphene-based hydrogen sulfide gas sensor can detect hydrogen sulfide gas with high sensitivity and high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a flow chart of a method for preparing a graphene-based hydrogen sulfide gas sensor in an embodiment of the present invention;

[0017] Figure 2 is a scanning electron microscope image of bimetallic oxide nanoparticles dispersed on the surface of each graphene layer in an embodiment of the present invention;

[0018] Figure 3 is a schematic structural diagram of a graphene-based hydrogen sulfide gas sensor according to an embodiment of the present invention;

[0019] Figure 4 2 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 1 of the present invention;

[0020] Figure 5 2 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 2 of the present invention;

[0021] Figure 6 3 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 3 of the present invention;

[0022] Figure 7 3 is a graph showing the response characteristics of the graphene-based hydrogen sulfide gas sensor to different concentrations of H2S in Example 3 of the present invention;

[0023] Figure 82 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 4 of the present invention;

[0024] Figure 9 4 is a cycle test curve diagram of the graphene-based hydrogen sulfide gas sensor in Example 4 of the present invention;

[0025] Figure 10 2 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 5 of the present invention;

[0026] Figure 11 2 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 6 of the present invention;

[0027] Figure 12 is a histogram showing the selectivity of the graphene-based hydrogen sulfide gas sensor to different gases in Example 6 of the present invention;

[0028] Figure 13 is a scanning electron microscope image of graphene modified with silver oxide and nickel oxide nanoparticles prepared under irradiation with laser beams of different powers in Example 7 of the present invention;

[0029] Figure 14 is a scanning electron microscope image of graphene modified with silver oxide and manganese oxide nanoparticles in Example 8 of the present invention;

[0030] Figure 15 2 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 9 of the present invention;

[0031] Figure 16 1 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 10 of the present invention;

[0032] Figure 17 1 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 11 of the present invention;

[0033] Figure 18 is a scanning electron micrograph of graphene modified with silver oxide and iron oxide nanoparticles in Example 12 of the present invention;

[0034] Figure 19 1 is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 12 of the present invention;

[0035] Figure 20This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 13 of the present invention.

[0036] In the drawings, the meanings of the reference numerals are as follows:

[0037] 1. Wooden base;

[0038] 2. Sensitive layer;

[0039] 3. Connect the electrodes. DETAILED DESCRIPTION

[0040] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concept of the present invention.

[0041] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The terms "comprise", "include", etc. used herein indicate the presence of the features, steps, operations and / or components, but do not exclude the presence or addition of one or more other features, steps, operations or components.

[0042] All terms used herein (including technical and scientific terms) have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0043] When expressions such as “at least one of A, B, and C, etc.” are used, they should generally be interpreted in accordance with the meaning commonly understood by those skilled in the art (for example, “a system having at least one of A, B, and C” should include but is not limited to systems having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, and C, etc.). When expressions such as “at least one of A, B, or C, etc.” are used, they should generally be interpreted in accordance with the meaning commonly understood by those skilled in the art (for example, “a system having at least one of A, B, or C” should include but is not limited to systems having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, and C, etc.).

[0044] To address the complex preparation process and the poor response of the resulting hydrogen sulfide gas sensor to ppb-level hydrogen sulfide gas, according to one aspect of the present invention, a wooden substrate is immersed in a mixed metal salt solution containing a water-soluble silver salt and a water-soluble transition metal salt. The immersed wooden substrate is then irradiated with a laser beam at room temperature without protective gas. When the laser beam strikes the surface of the wooden substrate, it absorbs the laser beam energy, which decomposes the lignin and cellulose in the wooden substrate. The carbon atoms in the lignin and cellulose decompose and reconstruct to form graphene. Simultaneously, the mixed metal salt immersed in the wooden substrate decomposes to form bimetallic oxide nanoparticles. The bimetallic oxide nanoparticles are dispersed on the surface of each graphene layer, forming a sensitive layer with high activity and selectivity. A conductive material is then coated on the wooden substrate and on both sides of the sensitive layer to form connecting electrodes in contact with the sensitive layer, thereby obtaining a graphene-based hydrogen sulfide gas sensor. This preparation process is simple and environmentally friendly, and the resulting graphene-based hydrogen sulfide gas sensor is capable of highly sensitive and selective detection of hydrogen sulfide gas.

[0045] Figure 1 is a flow chart of a method for preparing a graphene-based hydrogen sulfide gas sensor in an embodiment of the present invention, Figure 3 Schematic diagram of the structure of a graphene-based hydrogen sulfide gas sensor in an embodiment of the present invention.

[0046] According to an embodiment of the present invention, a method for preparing a graphene-based hydrogen sulfide gas sensor is provided, such as Figure 1 and Figure 3 As shown, the process includes the following steps S1 to S3.

[0047] Step S1: soaking the wooden substrate 1 in a mixed metal salt solution containing a water-soluble silver salt and a water-soluble transition metal salt.

[0048] According to an embodiment of the present invention, the wooden substrate 1 is any one of the following: basswood, oak and pine.

[0049] According to an embodiment of the present invention, the wooden substrate 1 is a wooden block of any size cut from natural wood.

[0050] In some specific embodiments, the wooden substrate 1 is cut into wooden blocks with a size of 1.5×4×5 cm.

[0051] Step S2: Using a laser beam to irradiate the soaked wooden substrate 1 at room temperature without protective gas, so that the lignin and cellulose in the wooden substrate 1 are cracked and reconstructed to form graphene, and at the same time, the mixed metal salt immersed in the wooden substrate 1 is decomposed to form bimetallic oxide nanoparticles. The bimetallic oxide nanoparticles are dispersed on the surface of each layer of graphene to obtain a sensitive layer, wherein the bimetallic oxide nanoparticles include silver oxide nanoparticles and transition metal oxide nanoparticles.

[0052] According to the embodiments of the present invention, wood is chosen as the substrate for laser beam-induced graphene formation for significant reasons. First, wood is easy to process. Its natural texture and structure eliminate the need for complex processing techniques, making cutting and polishing operations convenient and efficient, effectively reducing production costs and complexity. Second, it easily bonds with conductive materials (such as silver paste or metals), which is crucial for building high-performance electronic devices, ensuring interface stability and facilitating charge transfer. Third, wood has a carbon content between 40% and 70%, which stably provides sufficient carbon atoms to participate in the graphene formation reaction during laser beam induction, ensuring graphene yield and quality. A high carbon content (over 70%) can easily lead to excessive carbonization and defect formation, while a low carbon content (less than 20%) prevents the formation of a complete graphene structure. Wood effectively avoids these issues, providing a solid foundation for laser beam-induced high-quality graphene formation.

[0053] Figure 2 This is a scanning electron microscope image of bimetallic oxide nanoparticles dispersed on the surface of each graphene layer in an embodiment of the present invention.

[0054] According to an embodiment of the present invention, a soaked wood substrate 1 is irradiated using laser direct writing technology at room temperature without protective gas. When the laser beam is irradiated on the surface of the soaked wood substrate 1, the laser beam energy is absorbed. The energy is used to decompose the lignin and cellulose in the wood substrate 1. The carbon atoms in the lignin and cellulose are decomposed and reconstructed to form graphene. At the same time, the energy is used to decompose the mixed metal salt immersed in the wood substrate 1 to form bimetallic oxide nanoparticles, such as Figure 2 As shown, Figure 2 The white dots in the figure are bimetallic oxide nanoparticles, which are evenly distributed on the surface of each layer of graphene to obtain a sensitive layer 2. The sensitive layer 2 is a composite material of graphene and bimetallic oxide nanoparticles. The wooden substrate 1 provides support for the composite material of graphene and bimetallic oxide nanoparticles.

[0055] According to an embodiment of the present invention, graphene has good electrical conductivity, which is conducive to its response to the target gas at room temperature. In addition, graphene has a large specific surface area. Graphene is modified with bimetallic oxide nanoparticles as the sensitive layer 2. The bimetallic oxide nanoparticles can serve as adsorption sites for hydrogen sulfide gas molecules, greatly increasing the number of active sites of hydrogen sulfide gas molecules. The hydrogen sulfide gas molecules contact the bimetallic oxide nanoparticles and react with the adsorbed oxygen to cause electron transfer. At the same time, the bimetallic oxide nanoparticles can act as catalysts to allow more hydrogen sulfide gas molecules to be adsorbed on the graphene surface. The different Fermi levels between the hydrogen sulfide gas molecules and the graphene lead to electron transfer, thereby affecting the resistance of the sensitive layer 2. When detecting hydrogen sulfide gas at the ppb level, it has a high responsiveness and good selectivity.

[0056] According to an embodiment of the present invention, Ag has a greater adsorption energy for H2S molecules than other metals, making H2S more likely to adhere to the surface of the sensitive layer 2 and undergo electron transfer between it and the composite material of graphene and bimetallic oxide nanoparticles. Therefore, silver oxide nanoparticles, which have excellent affinity for H2S and catalytic activity, were selected as the sensing component. Transition metal oxides (manganese oxide, iron oxide, and nickel oxide) exhibit strong absorption within the laser beam wavelength range of 256nm to 760nm due to their dd electron transitions (electrons transitioning from a lower-energy d-orbital to a higher-energy d-orbital) and charge transfer. Therefore, transition metal oxides (manganese oxide, iron oxide, and nickel oxide) were selected as auxiliary catalysts. The synergistic effect of these two oxides enables highly selective detection of H2S.

[0057] Step S3: Coating a conductive material on the wooden substrate 1 and on both sides of the sensitive layer 2 to form a connecting electrode 3 in contact with the sensitive layer 2 to obtain a graphene-based hydrogen sulfide gas sensor.

[0058] According to an embodiment of the present invention, a wooden substrate 1 is immersed in a mixed metal salt solution containing a water-soluble silver salt and a water-soluble transition metal salt. The immersed wooden substrate 1 is irradiated with a laser beam at room temperature without protective gas. The wooden substrate 1 soaked in the mixed metal salt solution absorbs the energy of the laser beam when the laser beam is irradiated on the surface. The energy is used to decompose the lignin and cellulose in the wooden substrate 1, and the carbon atoms in the lignin and cellulose are decomposed and reconstructed to form graphene. At the same time, the mixed metal salt immersed in the wooden substrate 1 is decomposed to form bimetallic oxide nanoparticles. The bimetallic oxide nanoparticles are dispersed on the surface of each layer of graphene to obtain a sensitive layer with high activity and high selectivity, wherein the bimetallic oxide nanoparticles include silver oxide nanoparticles and transition metal oxide nanoparticles. A conductive material is coated on the wooden substrate 1 and on both sides of the sensitive layer 2 to form a connecting electrode 3 in contact with the sensitive layer 2, thereby obtaining a graphene-based hydrogen sulfide gas sensor. This method synthesizes graphene modified with bimetallic oxide nanoparticles in one step. The preparation process is simple and the material of the wooden substrate 1 is environmentally friendly, degradable, and easily recyclable, with low cost. The prepared graphene-based hydrogen sulfide gas sensor can detect hydrogen sulfide gas with high sensitivity and high selectivity, avoiding the problem of complex preparation process of composite materials of metal oxides or polymer nanoparticles and graphene in the existing gas sensing field.

[0059] According to an embodiment of the present invention, irradiating the soaked wooden substrate 1 with a laser beam at room temperature without protective gas includes: defining a target area on the surface of the soaked wooden substrate 1, and irradiating the target area with the laser beam. The target area can be any one of a point, a line, a circle, and a polygon.

[0060] According to an embodiment of the present invention, a target area is set on the surface of the soaked wooden substrate 1, and the target area is any one of a point, a line, a circle, a square and a rectangle, and then a laser beam is used to perform graphical induction on the target area.

[0061] According to an embodiment of the present invention, the wavelength of the laser beam is 256 nm to 760 nm, preferably the wavelength range of the laser beam is 480 nm to 760 nm, and the power of the laser beam is 0.5 W to 10 W.

[0062] According to an embodiment of the present invention, the wavelength of the laser beam can be selected as 256nm, 480nm, 760nm, etc. The power of the laser beam can be selected as 0.5W, 2W, 3W, 6W, 7W, 10W, etc. After extensive testing, when the laser beam wavelength is 256nm and the laser beam power is 0.5W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after the introduction of H2S, and the response to 200ppb H2S is 2.32%. When the laser beam wavelength is 256nm and the laser beam power is 6W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after the introduction of H2S, and the response to 200ppb H2S is 2.15%. When the laser beam wavelength is 480nm and the laser beam power is 2W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after the introduction of H2S, and the response to 200ppb H2S is 1.81%. When the laser beam had a wavelength of 532nm and a power of 10W, the resistance of the graphene-based hydrogen sulfide gas sensor increased after the introduction of H2S, and the response to 200ppb H2S was 1.89%. When the laser beam had a wavelength of 760nm and a power of 0.5W, the resistance of the graphene-based hydrogen sulfide gas sensor increased after the introduction of H2S, and the response to 200ppb H2S was 1.72%. When the laser beam had a wavelength of 760nm and a power of 10W, the resistance of the graphene-based hydrogen sulfide gas sensor increased after the introduction of H2S, and the response to 200ppb H2S was 1.77%.

[0063] According to an embodiment of the present invention, after a large number of tests, as the power of the laser beam increases, the bimetallic oxide nanoparticles gradually tend to agglomerate from a uniformly dispersed state. When the power of the laser beam exceeds 10W, the bimetallic oxide nanoparticles are completely agglomerated and cannot be distinguished.

[0064] According to an embodiment of the present invention, the water-soluble silver salt includes silver nitrate, and the water-soluble transition metal salt includes any one of the following: manganese nitrate, iron nitrate, and nickel nitrate.

[0065] According to an embodiment of the present invention, adding a water-soluble transition metal salt to the mixed metal salt solution can assist in absorbing the energy of the laser beam. This energy is used to decompose the lignin and cellulose in the wooden substrate 1, and the carbon atoms in the lignin and cellulose are rearranged to form graphene. At the same time, the mixed metal salt immersed in the wooden substrate 1 is decomposed to form bimetallic oxide nanoparticles.

[0066] According to an embodiment of the present invention, the silver oxide includes silver oxide, and the transition metal oxide includes any one of the following: manganese oxide, iron oxide, and nickel oxide.

[0067] According to an embodiment of the present invention, the wooden substrate 1 is immersed in a mixed metal salt solution of silver nitrate and manganese nitrate. The silver nitrate and manganese nitrate immersed in the wooden substrate 1 are transformed into silver oxide and manganese oxide nanoparticles under the irradiation of a laser beam.

[0068] According to an embodiment of the present invention, the wooden substrate 1 is immersed in a mixed metal salt solution of silver nitrate and iron nitrate. The silver nitrate and iron nitrate immersed in the wooden substrate 1 are transformed into silver oxide and iron oxide nanoparticles under the irradiation of a laser beam.

[0069] According to an embodiment of the present invention, the wooden substrate 1 is immersed in a mixed metal salt solution of silver nitrate and nickel nitrate. The silver nitrate and nickel nitrate immersed in the wooden substrate 1 are transformed into silver oxide and nickel oxide nanoparticles under the irradiation of a laser beam.

[0070] According to an embodiment of the present invention, the concentrations of the water-soluble silver salt and the water-soluble transition metal salt in the mixed metal salt solution are the same, and the concentration of the mixed metal salt solution is 0.1 mol / L to 2 mol / L.

[0071] According to an embodiment of the present invention, the concentration of the mixed metal salt solution can be selected, for example, from 0.1 mol / L, 1 mol / L, 1.4 mol / L, 1.8 mol / L, 2 mol / L, etc. Extensive testing has shown that as the concentration of the mixed metal salt solution increases, the bimetallic oxide nanoparticles gradually tend to agglomerate from a uniformly dispersed state. When the concentration of the mixed metal salt solution exceeds 2 mol / L, the bimetallic oxide nanoparticles are completely agglomerated and cannot be distinguished.

[0072] According to an embodiment of the present invention, the size of the bimetallic oxide nanoparticles is 30 nm to 1000 nm.

[0073] According to embodiments of the present invention, the size of the bimetallic oxide nanoparticles varies depending on the laser beam power and the concentration of the mixed metal salt solution. Extensive testing has shown that as the laser beam power increases, the bimetallic oxide nanoparticles gradually aggregate from a uniformly dispersed state. When the laser beam power exceeds 10W, the bimetallic oxide nanoparticles are completely aggregated and indistinguishable. As the concentration of the mixed metal salt solution increases, the bimetallic oxide nanoparticles gradually aggregate from a uniformly dispersed state. When the concentration of the mixed metal salt solution exceeds 2 mol / L, the bimetallic oxide nanoparticles are completely aggregated and indistinguishable.

[0074] According to an embodiment of the present invention, the conductive material includes a silver paste material and a metal material.

[0075] According to another embodiment of the present invention, Figure 3As shown, a graphene-based hydrogen sulfide gas sensor is provided. The sensor can be prepared using the aforementioned method for preparing a graphene-based hydrogen sulfide gas sensor. The sensor comprises a wooden substrate 1, a sensitive layer 2, and two connecting electrodes 3. The sensitive layer 2 is formed on the wooden substrate 1 and is a composite material of graphene and bimetallic oxide nanoparticles. The two connecting electrodes 3 are disposed on the wooden substrate 1, one on each side of the sensitive layer 2 and overlapping the sensitive layer 2.

[0076] According to an embodiment of the present invention, the detection range of the graphene-based hydrogen sulfide gas sensor for the concentration of hydrogen sulfide gas is 25ppb~500ppb.

[0077] According to an embodiment of the present invention, external hydrogen sulfide gas comes into contact with the sensitive layer 2, generating electron transfer, changing the conductivity of the sensitive layer 2, thereby affecting the resistance of the sensitive layer 2. The connecting electrodes 3 on both sides of the sensitive layer 2 facilitate testing the resistance of the sensitive layer 2 with a multimeter, thereby realizing the detection of hydrogen sulfide gas. The graphene-based hydrogen sulfide gas sensor prepared by the above method has excellent performance, good sensitivity, selectivity and stability for the detection of hydrogen sulfide gas, and can detect 25ppb~500ppb H2S with high sensitivity and high selectivity at room temperature, which is very conducive to its industrial development.

[0078] Example 1

[0079] This example uses oak as the wooden substrate 1. First, the oak wood is cut into 1.5×4×5 cm blocks, immersed in a 0.1 mol / L mixed metal salt solution of silver nitrate and manganese nitrate for 12 hours, and then oven-dried at 100°C for 4 hours. Laser direct writing technology is then used to pattern-generate graphene modified with silver oxide and manganese oxide nanoparticles on the wooden substrate 1 at room temperature without protective gas, forming the sensitive layer 2. The laser beam has a wavelength of 256 nm and a power of 0.5 W. After the sensitive layer 2 is prepared, it is attached to the printed circuit board (PCB) base using silver glue. This completes the fabrication of a hydrogen sulfide gas sensor based on graphene modified with silver oxide and manganese oxide nanoparticles, synthesized in one step on oak wood.

[0080] Subsequently, the prepared graphene-based hydrogen sulfide gas sensor was installed in a sealed cavity of known volume, tested at room temperature, and connected to an external digital multimeter. First, air was used as the background gas and introduced into the sealed cavity at a constant flow rate until the resistance of the graphene-based hydrogen sulfide gas sensor stabilized. After the resistance stabilized, the air flow rate was maintained unchanged, and the H2S gas valve was opened to allow the H2S and air to fully mix and then enter the sealed cavity and contact the graphene-based hydrogen sulfide gas sensor. At the same time, the timer was started and the change in the resistance of the graphene-based hydrogen sulfide gas sensor within the specified time was recorded. After the reaction was completed, the H2S gas valve was closed to allow the graphene-based hydrogen sulfide gas sensor to re-contact the air. The resistance recovery process was observed, and the next round of sensing tests was carried out after a certain recovery time.

[0081] Figure 4 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 1 of the present invention.

[0082] like Figure 4 As shown, when the wavelength of the laser beam is 256nm and the power of the laser beam is 0.5W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after H2S is introduced, and the response to 200ppb H2S is 2.32%.

[0083] Example 2

[0084] Different from Example 1, the wavelength of the laser beam used in this embodiment is 256 nm, and the power of the laser beam is 6 W.

[0085] Figure 5 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 2 of the present invention.

[0086] like Figure 5 As shown, when the wavelength of the laser beam is 256nm and the power of the laser beam is 6W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after H2S is introduced, and the response to 200ppb H2S is 2.15%.

[0087] Example 3

[0088] This embodiment uses basswood as the wooden substrate 1. First, the basswood is cut into 1.5×4×5 cm blocks, soaked in a 1 mol / L mixed metal salt solution of silver nitrate and ferric nitrate for 12 hours, and then placed in an oven to dry for 4 hours at 100°C. Laser direct writing technology is then used to pattern and induce the generation of graphene modified with silver oxide and iron oxide nanoparticles on the wooden substrate 1 at room temperature without protective gas, thereby obtaining a sensitive layer 2. The laser beam has a wavelength of 480 nm and a power of 2 W. After the sensitive layer 2 is prepared, it is attached to the PCB base using silver glue, thereby completing the production of a graphene-based hydrogen sulfide gas sensor modified with silver oxide and iron oxide nanoparticles synthesized in one step from basswood.

[0089] Subsequently, the prepared graphene-based hydrogen sulfide gas sensor was installed in a sealed cavity of known volume, tested at room temperature, and connected to an external digital multimeter. First, air was used as the background gas and introduced into the sealed cavity at a constant flow rate until the resistance of the graphene-based hydrogen sulfide gas sensor stabilized. After the resistance stabilized, the air flow rate was maintained unchanged, and the H2S gas valve was opened to allow the H2S and air to fully mix and then enter the sealed cavity and contact the graphene-based hydrogen sulfide gas sensor. At the same time, the timer was started and the change in the resistance of the graphene-based hydrogen sulfide gas sensor within the specified time was recorded. After the reaction was completed, the H2S gas valve was closed to allow the graphene-based hydrogen sulfide gas sensor to re-contact the air. The resistance recovery process was observed, and the next round of sensing tests was carried out after a certain recovery time.

[0090] Figure 6 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 3 of the present invention.

[0091] like Figure 6 As shown, when the wavelength of the laser beam is 480nm and the power of the laser beam is 2W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after H2S is introduced, and the response to 200ppb H2S is 1.81%.

[0092] Figure 7 3 is a graph showing the response characteristics of the graphene-based hydrogen sulfide gas sensor to different H2S concentrations in Example 3 of the present invention, wherein (a) is the response characteristic curve of H2S at concentrations of 25 ppb to 500 ppb, and (b) is a graph showing the responsivity of the graphene-based hydrogen sulfide gas sensor versus the test concentration.

[0093] like Figure 7 As shown, when the wavelength of the laser beam is 480nm and the power of the laser beam is 2W, Figure 7As shown in Figure (a), the graphene-based hydrogen sulfide gas sensor prepared in Example 3 responds to H2S with a concentration of 25ppb~500ppb. After the introduction of H2S, the resistance of the graphene-based hydrogen sulfide gas sensor increases, and as the concentration of H2S increases, the responsiveness of the graphene-based hydrogen sulfide gas sensor shows a clear upward trend. This shows that the graphene-based hydrogen sulfide gas sensor has good sensitivity to changes in the concentration of H2S. In addition, after each H2S test is completed, the graphene-based hydrogen sulfide gas sensor can quickly return to its initial state after the air is introduced, indicating that it has good stability and repeatability. Figure 7 As shown in Figure (b), at room temperature, the responsivity of the graphene-based hydrogen sulfide gas sensor corresponds one-to-one to the test concentration and has a good response.

[0094] Example 4

[0095] Different from Example 3, the wavelength of the laser beam used in this embodiment is 532 nm, and the power of the laser beam is 10 W.

[0096] Figure 8 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 4 of the present invention.

[0097] like Figure 8 As shown, when the wavelength of the laser beam is 532nm and the power of the laser beam is 10W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after H2S is introduced, and the response to 200ppb H2S is 1.89%.

[0098] Figure 9 This is a cyclic test curve diagram of the graphene-based hydrogen sulfide gas sensor in Example 4 of the present invention.

[0099] Using laser direct writing technology, graphene modified with silver oxide and iron oxide nanoparticles was patterned and induced on a wooden substrate 1 at room temperature without protective gas to obtain a sensitive layer 2. The wavelength of the laser beam was 532nm and the power of the laser beam was 10W. After the graphene-based hydrogen sulfide gas sensor was prepared, a cycle test was performed. Figure 9 As shown, it can be seen that the graphene-based hydrogen sulfide gas sensor has good stability after multiple cycle tests at room temperature.

[0100] Example 5

[0101] This embodiment uses pine wood as the wooden substrate 1. First, the pine wood is cut into wooden blocks of 1×4×5 cm in size, immersed in a 2 mol / L mixed metal salt solution of silver nitrate and nickel nitrate for 12 hours, and then placed in an oven for 4 hours at a drying temperature of 100°C. Laser direct writing technology is then used to pattern and induce the generation of graphene modified with silver oxide and nickel oxide nanoparticles on the wooden substrate 1 at room temperature without protective gas, thereby obtaining a sensitive layer 2. The wavelength of the laser beam is 760 nm, and the power of the laser beam is 0.5 W. After the sensitive layer 2 is prepared, the sensitive layer 2 is connected to the PCB base using silver glue, and the production of a graphene-based hydrogen sulfide gas sensor modified with silver oxide and nickel oxide nanoparticles synthesized in one step on pine wood is completed.

[0102] Subsequently, the prepared graphene-based hydrogen sulfide gas sensor was installed in a sealed cavity of known volume, tested at room temperature, and connected to an external digital multimeter. First, air was used as the background gas and introduced into the sealed cavity at a certain flow rate until the resistance of the graphene-based hydrogen sulfide gas sensor stabilized. After the resistance stabilized, the air flow rate was maintained unchanged, and the H2S gas valve was opened to allow the H2S and air to fully mix and then enter the sealed cavity and contact the graphene-based hydrogen sulfide gas sensor. At the same time, the timer was started and the change in the resistance of the graphene-based hydrogen sulfide gas sensor within the specified time was recorded. After the reaction was completed, the H2S gas valve was closed to allow the graphene-based hydrogen sulfide gas sensor to re-contact the air. The resistance recovery process was observed, and the next round of sensing tests was carried out after a certain recovery time.

[0103] Figure 10 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 5 of the present invention.

[0104] like Figure 10 As shown, when the wavelength of the laser beam is 760nm and the power of the laser beam is 0.5W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after H2S is introduced, and the response to 200ppb H2S is 1.72%.

[0105] Example 6

[0106] Different from Example 5, the wavelength of the laser beam used in this embodiment is 760 nm, and the power of the laser beam is 10 W.

[0107] Figure 11 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 6 of the present invention.

[0108] like Figure 11As shown, when the wavelength of the laser beam is 760nm and the power of the laser beam is 10W, the resistance of the graphene-based hydrogen sulfide gas sensor increases after H2S is introduced, and the response to 200ppb H2S is 1.77%.

[0109] Figure 12 This is a histogram showing the selectivity of the graphene-based hydrogen sulfide gas sensor to different gases in Example 6 of the present invention.

[0110] Using laser direct writing technology, graphene modified with silver oxide and nickel oxide nanoparticles was patterned and induced on a wooden substrate 1 at room temperature without protective gas to obtain a sensitive layer 2. The wavelength of the laser beam was 760nm and the power of the laser beam was 10W. After the graphene-based hydrogen sulfide gas sensor was prepared, the selectivity of the graphene-based hydrogen sulfide gas sensor for different gases was tested, such as Figure 12 As shown, it can be seen that the graphene-based hydrogen sulfide gas sensor has higher selectivity for H2S and lower response to other gases such as nitrogen dioxide (NO2), carbon monoxide (CO) and methane (CH4).

[0111] Example 7

[0112] In this embodiment, basswood material is used as the wood substrate 1 , and a scanning electron microscope (SEM) test is performed on the sensitive layer 2 synthesized in one step.

[0113] First, basswood was cut into 1.5 × 4 × 5 cm blocks and immersed in a 2 mol / L mixed metal salt solution of silver nitrate and nickel nitrate for 12 hours. The blocks were then oven-dried at 100°C for 4 hours. Laser direct writing technology was then used to generate graphene modified with silver oxide and nickel oxide nanoparticles on a wooden substrate (1) at room temperature without protective gas. The laser beam had a wavelength of 480 nm and was applied at powers of 0.5 W, 3 W, 7 W, and 10 W, respectively. After laser irradiation, the samples were subjected to SEM analysis.

[0114] Figure 13 3 and 4. These are scanning electron microscope images of graphene modified with silver oxide and nickel oxide nanoparticles prepared under irradiation with laser beams of different powers in Example 7 of the present invention.

[0115] like Figure 13 As shown in Figure (a), when the wavelength of the laser beam is 480nm and the power of the laser beam is 0.5W, the scanning electron microscope image of graphene modified with silver oxide and nickel oxide nanoparticles is shown. Figure 13 As shown in Figure (b), when the wavelength of the laser beam is 480nm and the power of the laser beam is 3W, the scanning electron microscope image of graphene modified with silver oxide and nickel oxide nanoparticles is obtained. Figure 13As shown in Figure (c), the scanning electron microscope image of graphene modified with silver oxide and nickel oxide nanoparticles when the wavelength of the laser beam is 480nm and the power of the laser beam is 7W. Figure 13 Figure (d) shows a scanning electron micrograph of graphene modified with silver oxide and nickel oxide nanoparticles when the laser beam has a wavelength of 480 nm and a power of 10 W. As the laser beam power increases, the silver oxide and nickel oxide nanoparticles gradually agglomerate from a uniformly dispersed state. When the laser beam power exceeds 10 W, the silver oxide and nickel oxide nanoparticles are completely agglomerated and cannot be distinguished.

[0116] Example 8

[0117] In this embodiment, pine wood material is used as the wood substrate 1, and a scanning electron microscope (SEM) test is performed on the sensitive layer 2 synthesized in one step.

[0118] First, pine wood blocks measuring 1.5 × 4 × 5 cm were cut and immersed in mixed metal salt solutions of silver nitrate and manganese nitrate at varying concentrations for 12 hours (the concentrations were 0.1 mol / L, 0.8 mol / L, 1 mol / L, 1.4 mol / L, 1.8 mol / L, and 2 mol / L, respectively). The blocks were then oven-dried for 4 hours at 100°C. Laser direct writing technology was then used to generate graphene modified with silver oxide and manganese oxide nanoparticles on a wooden substrate (1) at room temperature without protective gas. The laser beam had a wavelength of 760 nm and a power of 0.5 W. After laser irradiation, the samples were subjected to SEM analysis.

[0119] Figure 14 This is a scanning electron microscope image of graphene modified with silver oxide and manganese oxide nanoparticles in Example 8 of the present invention.

[0120] like Figure 14 As shown in Figure (a), when the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate is 0.1 mol / L, the scanning electron microscope image of graphene modified with silver oxide and manganese oxide nanoparticles is obtained. Figure 14 As shown in Figure (b), when the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate is 0.8 mol / L, the scanning electron microscope image of graphene modified with silver oxide and manganese oxide nanoparticles is obtained. Figure 14 As shown in Figure (c), when the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate is 1 mol / L, the scanning electron microscope image of graphene modified with silver oxide and manganese oxide nanoparticles is obtained. Figure 14 As shown in Figure (d), when the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate is 1.4 mol / L, the scanning electron microscope image of graphene modified with silver oxide and manganese oxide nanoparticles is obtained. Figure 14As shown in Figure (e), when the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate is 1.8 mol / L, the scanning electron microscope image of graphene modified with silver oxide and manganese oxide nanoparticles is obtained. Figure 14 Figure (f) shows a scanning electron micrograph of graphene modified with silver oxide and manganese oxide nanoparticles when the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate is 2 mol / L. As the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate increases, the silver oxide and manganese oxide nanoparticles gradually tend to agglomerate from a uniformly dispersed state. When the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate exceeds 2 mol / L, the silver oxide and manganese oxide nanoparticles have completely agglomerated and cannot be distinguished.

[0121] Example 9

[0122] This embodiment uses oak as the wooden substrate 1. First, the oak is cut into blocks of 1×4×5 cm in size, immersed in a 2 mol / L mixed metal salt solution of silver nitrate and nickel nitrate for 12 hours, and then placed in an oven for 4 hours at 100°C. Laser direct writing technology is then used to pattern and induce the generation of graphene modified with silver oxide and nickel oxide nanoparticles on the wooden substrate 1 at room temperature without protective gas, thereby obtaining a sensitive layer 2. The wavelengths of the laser beam are 256 nm, 480 nm, 760 nm, and 1064 nm, respectively, and the power of the laser beam is 0.5 W. After the sensitive layer 2 is prepared, the sensitive layer 2 is connected to the PCB base using silver glue, and the graphene-based hydrogen sulfide gas sensor modified with silver oxide and nickel oxide nanoparticles synthesized in one step on oak is completed.

[0123] Subsequently, the prepared graphene-based hydrogen sulfide gas sensor was installed in a sealed cavity of known volume, tested at room temperature, and connected to an external digital multimeter. First, air was used as the background gas and introduced into the sealed cavity at a certain flow rate until the resistance of the graphene-based hydrogen sulfide gas sensor stabilized. After the resistance stabilized, the air flow rate was maintained unchanged, and the H2S gas valve was opened to allow the H2S and air to fully mix and then enter the sealed cavity and contact the graphene-based hydrogen sulfide gas sensor. At the same time, the timer was started and the change in the resistance of the graphene-based hydrogen sulfide gas sensor within the specified time was recorded. After the reaction was completed, the H2S gas valve was closed to allow the graphene-based hydrogen sulfide gas sensor to re-contact the air. The resistance recovery process was observed, and the next round of sensing tests was carried out after a certain recovery time.

[0124] Figure 15 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 9 of the present invention.

[0125] like Figure 15As shown, the response of the graphene-based hydrogen sulfide gas sensor to H2S first increases and then decreases with increasing laser beam wavelength. This may be due to the higher photon energy at shorter laser beam wavelengths, which can lead to local overheating or excessive carbonization of the material. The resulting graphene contains more lattice defects, which affect charge transfer and adsorption between H2S molecules and the graphene. As the laser beam wavelength gradually increases, the photon energy decreases, better matching the absorption peaks of the wood substrate 1 and the mixed metal salts (silver nitrate and nickel nitrate). This provides ample time for carbon atoms to restructure at a suitable temperature, resulting in a high-quality composite of graphene and bimetallic oxide nanoparticles (silver oxide and nickel oxide nanoparticles). This reduces lattice defects and results in more uniform graphene layers, improving gas-sensing performance. The optimal laser beam wavelength range tested is 480nm to 760nm. As the laser beam wavelength continues to increase, the laser energy may be insufficient, resulting in a weakened graphitization of the wood substrate 1 and an increase in defects, which in turn reduces the response to H2S. When the wavelength of the laser beam is 1064nm, the photon energy is too low, and the induction process mainly relies on thermal effects rather than light excitation effects. The induction efficiency is poor, the generated graphene has more defects, the crystal quality is low, and the conductivity and chemical activity are significantly reduced, resulting in the graphene-based hydrogen sulfide gas sensor being unable to respond to H2S.

[0126] Example 10

[0127] This embodiment uses basswood as the wooden substrate 1. First, the basswood is cut into blocks measuring 1×4×5 cm, immersed in a 1.5 mol / L mixed metal salt solution of silver nitrate and manganese nitrate for 12 hours, and then placed in an oven to dry for 4 hours at 100°C. Laser direct writing technology is then used to pattern and induce the generation of graphene modified with silver oxide and manganese oxide nanoparticles on the wooden substrate 1 at room temperature without protective gas, thereby obtaining a sensitive layer 2. The laser beam has a wavelength of 256 nm and a power of 18 W. After the sensitive layer 2 is prepared, it is attached to the PCB base using silver glue, thereby completing the fabrication of a graphene-based hydrogen sulfide gas sensor modified with silver oxide and manganese oxide nanoparticles synthesized in one step from basswood.

[0128] Subsequently, the prepared graphene-based hydrogen sulfide gas sensor was installed in a sealed cavity of known volume, tested at room temperature, and connected to an external digital multimeter. First, air was used as the background gas and introduced into the sealed cavity at a certain flow rate until the resistance of the graphene-based hydrogen sulfide gas sensor stabilized. After the resistance stabilized, the air flow rate was maintained unchanged, and the H2S gas valve was opened to allow the H2S and air to fully mix and then enter the sealed cavity and contact the graphene-based hydrogen sulfide gas sensor. At the same time, the timer was started and the change in the resistance of the graphene-based hydrogen sulfide gas sensor within the specified time was recorded. After the reaction was completed, the H2S gas valve was closed to allow the graphene-based hydrogen sulfide gas sensor to re-contact the air. The resistance recovery process was observed, and the next round of sensing tests was carried out after a certain recovery time.

[0129] Figure 16 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 10 of the present invention.

[0130] like Figure 16 As shown in the figure, when the laser beam power is 18W, the graphene-based hydrogen sulfide gas sensor no longer responds to H2S. This may be because when the laser beam power is too high, the high temperature causes the bimetallic oxide nanoparticles (silver oxide and manganese oxide nanoparticles) to melt or sinter, resulting in an increase in particle size and a significant decrease in specific surface area, which reduces the number of active sites for H2S adsorption and, in turn, causes the graphene-based hydrogen sulfide gas sensor to fail to respond to H2S.

[0131] Example 11

[0132] This embodiment uses pine wood as the wooden substrate 1. First, the pine wood is cut into blocks of 1×4×5 cm in size, immersed in a mixed metal salt solution of silver nitrate and manganese nitrate at a concentration of 5 mol / L for 12 hours, and then placed in an oven for 4 hours at a drying temperature of 100°C. Laser direct writing technology is then used to pattern and induce the generation of graphene modified with silver oxide and manganese oxide nanoparticles on the wooden substrate 1 at room temperature without protective gas, thereby obtaining a sensitive layer 2. The wavelength of the laser beam is 480 nm, and the power of the laser beam is 6 W. After the sensitive layer 2 is prepared, the sensitive layer 2 is connected to the PCB base using silver glue, and the production of a graphene-based hydrogen sulfide gas sensor modified with silver oxide and manganese oxide nanoparticles synthesized in one step on pine wood is completed.

[0133] Subsequently, the prepared graphene-based hydrogen sulfide gas sensor was installed in a sealed cavity of known volume, tested at room temperature, and connected to an external digital multimeter. First, air was used as the background gas and introduced into the sealed cavity at a certain flow rate until the resistance of the graphene-based hydrogen sulfide gas sensor stabilized. After the resistance stabilized, the air flow rate was maintained unchanged, and the H2S gas valve was opened to allow the H2S and air to fully mix and then enter the sealed cavity and contact the graphene-based hydrogen sulfide gas sensor. At the same time, the timer was started and the change in the resistance of the graphene-based hydrogen sulfide gas sensor within the specified time was recorded. After the reaction was completed, the H2S gas valve was closed to allow the graphene-based hydrogen sulfide gas sensor to re-contact the air. The resistance recovery process was observed, and the next round of sensing tests was carried out after a certain recovery time.

[0134] Figure 17 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 11 of the present invention.

[0135] like Figure 17 As shown in the figure, when the concentration of the mixed metal salt solution of silver nitrate and manganese nitrate is 5 mol / L, the graphene-based hydrogen sulfide gas sensor no longer responds to H2S. This may be because when the concentration is too high (greater than 2 mol / L), the local heat accumulation of the bimetallic salts (silver nitrate and manganese nitrate) during laser irradiation intensifies, causing the bimetallic oxide nanoparticles (silver oxide and manganese oxide nanoparticles) to melt and agglomerate. The specific surface area of ​​the bimetallic oxide nanoparticles (silver oxide and manganese oxide nanoparticles) decreases significantly, reducing the number of active sites for H2S adsorption, and thus causing the graphene-based hydrogen sulfide gas sensor to fail to respond to H2S.

[0136] Example 12

[0137] This example uses pine wood as the wooden substrate 1. First, the pine wood was cut into blocks measuring 1×4×5 cm and immersed in a 5 mol / L mixed metal salt solution of silver nitrate and iron nitrate for 12 hours. The blocks were then oven-dried at 100°C for 4 hours. Laser direct writing technology was then used at room temperature and without protective gas to pattern graphene modified with silver oxide and iron oxide nanoparticles onto the wooden substrate 1, forming the sensitive layer 2. The laser beam had a wavelength of 1064 nm and a power of 18 W. After the sensitive layer 2 was completed, SEM analysis was performed.

[0138] Figure 18 3 is a scanning electron microscope image of graphene modified with silver oxide and iron oxide nanoparticles in Example 12 of the present invention.

[0139] like Figure 18As shown in , the silver oxide and iron oxide nanoparticles have partially aggregated into agglomerates, and the particle size is more than 1000 nm.

[0140] After the test, the sensitive layer 2 was connected to the PCB base using silver glue, and the graphene-based hydrogen sulfide gas sensor modified with silver oxide and iron oxide nanoparticles synthesized in one step based on pine wood was completed.

[0141] Subsequently, the prepared graphene-based hydrogen sulfide gas sensor was installed in a sealed cavity of known volume, tested at room temperature, and connected to an external digital multimeter. First, air was used as the background gas and introduced into the sealed cavity at a certain flow rate until the resistance of the graphene-based hydrogen sulfide gas sensor stabilized. After the resistance stabilized, the air flow rate was maintained unchanged, and the H2S gas valve was opened to allow the H2S and air to fully mix and then enter the sealed cavity and contact the graphene-based hydrogen sulfide gas sensor. At the same time, the timer was started and the change in the resistance of the graphene-based hydrogen sulfide gas sensor within the specified time was recorded. After the reaction was completed, the H2S gas valve was closed to allow the graphene-based hydrogen sulfide gas sensor to re-contact the air. The resistance recovery process was observed, and the next round of sensing tests was carried out after a certain recovery time.

[0142] Figure 19 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 12 of the present invention.

[0143] like Figure 19 As shown in Figure 2, when the silver oxide and iron oxide nanoparticles exceed 1000nm in size, the graphene-based hydrogen sulfide gas sensor no longer responds to H2S. This may be because when the particle size is too large, the specific surface area decreases, reducing the number of exposed active sites. At the same time, the large particles have lower surface energy, which reduces the adsorption of H2S and thus leads to the inability to respond to H2S.

[0144] Example 13

[0145] This embodiment uses pine wood as the wooden substrate 1. First, the pine wood is cut into blocks of 1×4×5 cm in size, immersed in a mixed metal salt solution of tin nitrate and chromium nitrate at a concentration of 1 mol / L for 12 hours, and then placed in an oven for 4 hours at a drying temperature of 100°C. Laser direct writing technology is then used to pattern and induce the generation of graphene modified with tin oxide and chromium oxide nanoparticles on the wooden substrate 1 at room temperature without protective gas, thereby obtaining a sensitive layer 2. The wavelength of the laser beam is 480 nm, and the power of the laser beam is 6 W. After the sensitive layer 2 is prepared, the sensitive layer 2 is connected to the PCB base using silver glue, and the graphene-based hydrogen sulfide gas sensor modified with tin oxide and chromium oxide nanoparticles synthesized in one step on pine wood is completed.

[0146] Subsequently, the prepared graphene-based hydrogen sulfide gas sensor was installed in a sealed cavity of known volume, tested at room temperature, and connected to an external digital multimeter. First, air was used as the background gas and introduced into the sealed cavity at a certain flow rate until the resistance of the graphene-based hydrogen sulfide gas sensor stabilized. After the resistance stabilized, the air flow rate was maintained unchanged, and the H2S gas valve was opened to allow the H2S and air to fully mix and then enter the sealed cavity and contact the graphene-based hydrogen sulfide gas sensor. At the same time, the timer was started and the change in the resistance of the graphene-based hydrogen sulfide gas sensor within the specified time was recorded. After the reaction was completed, the H2S gas valve was closed to allow the graphene-based hydrogen sulfide gas sensor to re-contact the air. The resistance recovery process was observed, and the next round of sensing tests was carried out after a certain recovery time.

[0147] Figure 20 This is a graph showing the real-time response characteristics of the graphene-based hydrogen sulfide gas sensor to 200 ppb H2S in Example 13 of the present invention.

[0148] like Figure 20 As shown, the graphene-based hydrogen sulfide gas sensor is unresponsive to H2S. This may be because tin oxide and chromium oxide nanoparticles lack good affinity and catalytic activity for H2S, preventing them from reacting with H2S and generating a response. However, the present invention utilizes silver oxide nanoparticles, which have good affinity and catalytic activity for H2S, as the sensing component, and transition metal oxides as auxiliary catalysts to assist in laser absorption. The synergistic effect of these two components ultimately enables the development of a graphene-based hydrogen sulfide gas sensor capable of highly sensitive and selective H2S detection via a simple and efficient one-step laser induction method.

[0149] The above describes embodiments of the present invention. However, these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention. Although each embodiment has been described separately above, this does not mean that the measures in each embodiment cannot be advantageously used in combination. The scope of the present invention is defined by the appended claims and their equivalents. Without departing from the scope of the present invention, those skilled in the art may make various substitutions and modifications, which are intended to fall within the scope of the present invention.

Claims

1. A method for preparing a graphene-based hydrogen sulfide gas sensor, characterized in that: include: soaking the wooden substrate in a mixed metal salt solution comprising a water-soluble silver salt and a water-soluble transition metal salt; Irradiating the soaked wood substrate with a laser beam at room temperature without protective gas to decompose and reconstruct lignin and cellulose in the wood substrate to form graphene, while simultaneously decomposing the mixed metal salt immersed in the wood substrate to form bimetallic oxide nanoparticles, wherein the bimetallic oxide nanoparticles are dispersed on the surface of each graphene layer to obtain a sensitive layer, wherein the bimetallic oxide nanoparticles include silver oxide nanoparticles and transition metal oxide nanoparticles; Conductive material is coated on the wooden substrate and on both sides of the sensitive layer to form connecting electrodes in contact with the sensitive layer, thereby obtaining a graphene-based hydrogen sulfide gas sensor.

2. The preparation method according to claim 1, characterized in that The wooden substrate is any one of the following: basswood, oak, and pine.

3. The preparation method according to claim 1, characterized in that The wavelength of the laser beam is 256 nm to 760 nm, and the power of the laser beam is 0.5 W to 10 W.

4. The preparation method according to claim 1, characterized in that The water-soluble silver salt includes silver nitrate; The water-soluble transition metal salt includes any one of the following: manganese nitrate, iron nitrate and nickel nitrate.

5. The preparation method according to claim 4, characterized in that The water-soluble silver salt and the water-soluble transition metal salt have the same concentration in the mixed metal salt solution, and the concentration of the mixed metal salt solution is 0.1 mol / L to 2 mol / L.

6. The preparation method according to claim 1, characterized in that Silver oxides include silver oxide; The transition metal oxide includes any of the following: manganese oxide, iron oxide, and nickel oxide.

7. The preparation method according to claim 1, characterized in that The size of the bimetallic oxide nanoparticles is 30nm-1000nm.

8. The preparation method according to claim 1, characterized in that The conductive material includes silver paste material and metal material.

9. A graphene-based hydrogen sulfide gas sensor, characterized in that: Prepared by the preparation method of the graphene-based hydrogen sulfide gas sensor according to any one of claims 1 to 8, the graphene-based hydrogen sulfide gas sensor comprises: wooden base; A sensitive layer is formed on the wooden substrate, wherein the sensitive layer is a composite material of graphene and bimetallic oxide nanoparticles; Two connecting electrodes are arranged on the wooden substrate, are respectively located on both sides of the sensitive layer, and overlap with the sensitive layer.

10. The graphene-based hydrogen sulfide gas sensor according to claim 9, characterized in that: The detection range of the graphene-based hydrogen sulfide gas sensor for the concentration of hydrogen sulfide gas is 25ppb~500ppb.

Citation Information

Patent Citations

  • Precious metal / base metal oxide / graphene ternary composite gas sensitive material and preparation method thereof

    CN105158303A

  • Method for producing iron oxide cooperated nano-silver / graphene oxide SERS substrate

    CN108414495A

  • Methods of fabricating laser-induced graphene and compositions thereof

    CN110167877A

  • Wood-based flexible electrode, preparation method and application thereof

    CN111640586A

  • Preparation method of laser-induced graphene on wood

    CN114275772A

Cited By

  • Graphene-based nitrogen dioxide gas sensor and preparation method thereof

    CN120721805A

  • Graphene-based nitrogen dioxide gas sensor and method of making the same

    CN120721805B